A Comprehensive Understanding on How Ultrathin Coating Layers on Active Particles Enhance Battery Performance Significantly. (7th July 2017) - Sarkar, Susmita; Patel, Rajankumar L.; Liang, Xinhua; Park, Jonghyun
Abstract : Although atomic layer deposition (ALD) coating strategies for active materials in lithium ion batteries are more effective than other coating techniques to improve battery performance, there is substantial uncertainty as to how such coatings are a source of improved performance. A comprehensive model has been developed based on experimental measurements and theoretical analysis to study the effects of various coating strategies on the mechanical and electrochemical reactions of battery systems. Thicker coatings can help provide higher capacity and cycle life improvements, but too thick layers can act as a migration barrier, causing much slower lithium transport, resulting in reduced capacity. In addition, the developed model quantitatively predicts the capacity retention of coated particles by mitigating the dissolution of transition metal ions, which is one important capacity of the metal oxide cathode materials. Experimental observation of coated and uncoated LiMn2 O4 -Li foil cells supports our framework for modeling and understanding the contribution of thin coatings to the improved behavior of cathode particles.